Thermodynamic Analysis of Self-Ignition in Spark-Ignited Engines Operated with Alternative Gaseous Fuels - Duarte, Jorge; Orozco, Wilman; González, Jorge; Buelvas, Edgardo; Corredor, Lesme (TECCIENCIA, 2016)
Currently, detailed studies exist on the self-ignition phenomenon in liquid fuels and even for natural gas. However, studies for syngas are quite limited and existing ones are mainly focused on combustion kinetics and do not study self-ignition prior to the ignition point. This paper presents the development of a thermodynamic analysis to study the self-ignition phenomenon in gaseous alternative fuels during the compression stroke in spark-ignited internal combustion engines. Analysis takes into account the fuel composition, relevant process parameters, and variation due to pressure and temperature intake changes. The approach is focused on equilibrium thermodynamics, which easily allows estimating engine operating conditions. These results permit studying adequate compression ratios to obtain good efficiencies, as those achieved by using natural gas, but in heat engine applications to generate power with low-methane-number syngas fuels.